АРАБЧА СИНИҚ КЎПЛИК ВАЗНИДАГИ ЎЗЛАШМА СЎЗЛАР ВА УЛАРНИНГ СЕМАНТИК ХУСУСИЯТЛАРИ (Scientific journal of the Fergana State University, 2023)
This article deals with semantic and stylistic peculiarities of some arabic borrowings in broken plural forms.